Novel, Speedy, and Eco-Friendly Carboxymethyl Cellulose-Nitrogen Doped Carbon Dots Biosensors with DFT Calculations, Molecular Docking, and Experimental Validation - Hebat-Allah S. Tohamy (Gels)
Carboxymethyl cellulose (CMC) was prepared from sugarcane bagasse (SB) in minutes using a novel microwave method. Additionally, nitrogen-doped carbon dots (N–CDs) were synthesized from SB using the same microwave technique. These materials were crosslinked with CaCl2 to prepare antibacterial/antifungal hydrogel sensors. In this regard, both CMC@Ca and CMC@Ca-N–CDs exhibited antibacterial activity against Escherichia coli (Gram negative), while only CMC@Ca-N–CDs demonstrated antibacterial activity against Staphylococcus aureus (Gram positive). Moreover, both materials showed antifungal activity against Candida albicans. The molecular docking study demonstrated that CMC@Ca-N–CDs showed good binding with proteins with short bond length 2.59, 2.80, and 1.97 A° for Escherichia coli, Staphylococcus aureus, and Candida albicans, respectively. These binding affinities were corroborated by the observed inhibition zone diameters. Furthermore, fluorescence microscope revealed distinct imaging patterns between Gram-positive and Gram-negative bacteria, as well as pathogenic yeast (fungi). CMC@Ca-N–CDs emitted blue light when exposed to Escherichia coli and Candida albicans (i.e., CMC@Ca-N–CDs/Escherichia coli and Candida albicans), whereas it emitted bright-red light when exposed to Staphylococcus aureus (i.e., CMC@Ca-N–CDs/Staphylococcus aureus). This disparity in the fluorescence-emitted colors is due to the difference in the cell wall of these microorganisms. Additionally, DFT calculations were conducted to substantiate the robust chemical interactions between CMC, Ca2+, and N–CDs.